Design of Android-Based PAI Learning Media Using Mit App Inventor in Class X SMAN 1 Pasaman Regency - Efprianti, Nera; Supriadi, Supriadi; Zakir, Supratman; Efriyanti, Liza (Pusdikra Publishing, 2024)
This research focuses on the problem of limited use of technology in Islamic religious education media which was previously used at SMAN 1 Panti. The aim of using Mit App Inventor in the learning media for the Android-based Islamic Religious Education program is to help teachers maximize the use of Mit App Inventor in teaching media and increase student motivation in taking Islamic Education lessons. This research uses any recognized research and development methodology. In this research, the author uses the 4D design paradigm, Define, Design, Develop, and Disseminate. The results of this study use the Aikens V hypothesis for assessing validity, the Moment Kappa hypothesis for assessing practice, and the R.Hake hypothesis (G-Score) for assessing effectiveness. Validity test results with a minimum score of 0.87 indicate the test is valid. Effectiveness testing which is said to be